Aortic distensibility and left ventricular diastolic functions in endurance athletes - Kasikcioglu, E.; Kayseriloglu, A.; Oflaz, H.; Akhan, H. (International Journal of Sports Medicine, 2005)
Aortic elastic properties are important determinants of left ventricular function. The aim of this study was to determine left ventricular diastolic function and aortic distensibility in endurance athletes. Thirty male runners and thirty age-matched healthy male controls took part in the study. All subjects underwent echocardiographic examination and cardiopulmonary exercise testing. Measurements included LV cavity dimension, standard and tissue Doppler parameters, and aortic diameter, 3 cm above aortic valve, at systole and diastole. Maximal oxygen uptake in athletes was higher than in controls. The aortic distensibility index was found to be higher in athletes compared with controls (5.37 ± 1.50 vs. 3.37 ± 1.48 cm2 · dynes-1 · 10-6, p < 0.001). While the aortic stiffness index in athletes was significantly lower than in controls (2.77 ± 0.28 vs. 3.43 ± 0.41, p < 0.001). Furthermore, transmitral early peak velocity (E) and late peak velocity (A), peak velocity of myocardial systolic wave (Sm), early (Em) and atrial (Am) diastolic waves in athletes were higher than in controls. It seemed that the association of Em velocity with aortic distensibility was stronger than that of other LV parameters (coefficient = 0.74, p < 0.001) by using multiple linear regression. Increased aortic distensibility in endurance-trained athletes may cause better diastolic function as a physiological cardiovascular adaptation factor.